SOURCE AND SUPPLY OF TEACHERS. - Johnson, Arnold W. (The Accounting Review, 1957)
Abstract The author of this article examines the source and supply of teachers. He emphasizes on the publicization of teaching as a career recommending that every staff member of a school of business administration should advertise the advantages of the teaching profession. The second point he highlights is making the profession more attractive by increasing salary scales, recognition of good teaching and productivity, and encouragement of ways to promote greater efficiency. Thirdly he emphasizes on the encouragement of graduate work leading to teaching careers which include financial assistance for students, procurement of master's degree, realistic doctoral programs for potential teachers. Fourthly, he recommends the encouragement of experienced public accountants to assume teaching duties. He also recommends the encouragement of ex-teachers to assume full or part-time teaching responsibilities, tapping non-accountant sources which are related discipline for teaching assistance and using retired qualified talents. He finally proposes the re-examination of the demand for teachers by noting several points.